Diseminasi Hasil Riset Anti Mikroba Alami Berbasis Pemanfaatan Limbah Kulit Buah Menjadi Hand Sanitizer Di Sentra Industri Keripik Pisang - Dewi Sartika; Susilawati; Neti Yuliana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The Center for Home Industry chips on Bandar Lampung. The problem of this is the waste that has not been managed properly, the chip waste IRT waste in the form of fruit peels, leaves, fruit stalks, humps has the potential to be made of high-selling value products, diversification can be in the form of hand sanitizer products. The purpose of this activity is to solve the Partner's problem by disseminating research results in the form of transfer of waste treatment technology into a hand sanitizer. The method used is lectures and discussions on the dissemination of research results, assistance in processing wastewater into hand sanitizer products. The need for partners to process waste products into products that have value in the form of making herbal solid soap, followed by liquid soap, hand sanitizer, natural anti-microbial, feed making, composting and liquid fertilizer. The percentage increase in knowledge and understanding of the material after the service activities is the utilization of waste (40%), making feed (50%), making hand sanitizer (70%).